Sorption and Desorption Behaviour of Chromium in Soils of Punjab - and Kuldip-Singh, Satnam Kaur, Dhanwinder-Singh* (Journal of the Indian Society of Soil Science, 2021)
The present study was carried out to understand soil chromium (Cr) sorption/desorption phenomena, and hence Cr bioavailability in surface soils collected from Jalandhar, Ludhiana and Mandi Gobindgarh in Punjab. Chromium sorption isotherms were derived by sorption of Cr from solutions containing a range of concentrations equivalent to 50, 100, 300 600 and 900 Âµg Cr g-1 soil in the presence of a background electrolyte, 0.01 M Ca(NO3)2. Chromium desorption isotherms were derived from the Cr desorbed (Âµg gâ€1 soil) after each of five desorption periods, carried out by sequentially equilibrating same soil samples used for Cr sorption study in Cr-free 0.01 M Ca(NO3)2. It was observed that with the increase in rate of Cr application, amount of Cr sorbed by the soils also increased; however, the per cent Cr sorbed decreased. The Cr sorption data of the three selected soil samples were best described by Freundlich (R2 = 0.986 to 0.994) followed by Langmuir (R2 = 0.959 to 0.995), and Dubininâ€“Radushkevich (D-R) adsorption isotherms (R2 = 0.926 to 0.973). The constants measuring adsorption capacity, derived from all the three adsorption isotherms, indicated that the soil from Mandi Gobindgarh has higher Cr sorption capacity than the other two soils. Desorption of Cr as well as per cent Cr desorbed from the selected soils increased with the increase in added Cr concentration. The Cr desorption data of the soils were very well described by Langmuir desorption isotherm (R2 = 0.96 to 0.99). Desorption maxima derived was also observed to be higher in case of Mandi Gobingarh soil which implies that this soil has maximum desorption capacity. The differences in amounts of Cr sorbed and desorbed by experimental soils may be due to variation in soil parameters such as organic carbon and cation exchange capacity.